Mapping Risk Level Based on Peak Ground Acceleration (PGA) and Earthquake Intensity Using Multievent Earthquake Data in Malang Regency, East Java, Indonesia - Uswatun Chasanah; Eko Handoyo; Nesya Nuur Rahmawati; Masria Musfiana (Jurnal Ilmu Fisika (JIF), 2022)
This research aimed to identify the earthquake hazard, developing a peak ground acceleration (PGA) and earthquake intensity map to reduce earthquake disaster risk in Malang, East Java, Indonesia. This map is based on historical data of earthquake occurrence in 2011-2021 using the International Seismological Centre (ISC) earthquake catalog. Peak ground acceleration was analyzed using Donovan and McGuire equation, and the earthquake intensity was analyzed using the Wald equation. The result of this study represented peak ground acceleration value in Malang Regency, which was varied from 23.687 – 33.069 gal (Donovan attenuation equation) and 22.245 – 31.705 gal (McGuire attenuation equation). While based on earthquake depth, Malang Regency had a damage capacity of IV-V MMI on an intensity scale. This intensity was equivalent to the formation of cracks in the ground. Almost all residents also feel the vibrations. The most severe damage was due to the earthquake on April 10, 2021, at 14:00:16 WIB spoiled Dampit and Bantur district's public facilities. This study provides an overview of the riskiest area affected by the disasters that can be used for disaster mitigation in Malang regency.